PENGARUH KESADARAN, PERSEPSI DAN PREFERENSI KONSUMEN TERHADAP PERILAKU KONSUMEN DALAM MENGKONSUMSI BUAH LOKAL DI KAWASAN PERPASARAN JAKARTA BARAT - Nailul Murod; Siti Rochaeni; Lilis Imamah Ichdayati (Departement of Agribusiness Faculty of Science and Technology, 2018)
The purpose of this study is to determine the effect of consciousnesses, perceptions, and consumer preferences on consumer behaviors in consuming local fruits. The research was conducted in Slipi, Hypermart Puri Indah, Supermarket Kebon Jeruk, Minimarket in Kembangan area, and Specialty Stores of Rezeky Fresh Fruit Center. A total of 100 respondents were interviewed by using accidental sampling technique. Analysis descriptions and multiple regression analysis were employed to analyze the data. The results showed that the variables of consciousnesses, perceptions and customer preferences significantly affect consumer behavior in consuming local fruit.